PENGARUH PENDEKATAN MINDFUL LEARNING TERHADAP HASIL BELAJAR IPAS KELAS V SEKOLAH DASAR - Abdurrochim, Putri Laisya; Hanifah, Nurdinah; Syahid, Aah Ahmad (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Elementary schools' IPAS (Natural and Social Sciences) learning process still emphasizes transforming factual information and developing verbalistic reasoning. Also, the presentation process has yet to be integrated, as science and social studies are still taught separately, and its evaluation process is still based on students' comprehension of a concept. This study aims to analyze the effect of a mindful learning approach on science and social studies (IPAS) learning outcomes in the fifth-grade elementary school class focusing on the topic "Daerahku Kebanggaanku" with the subtopic A: "Seperti Apakah Budaya Daerahku?". The study samples, selected using purposive non-random sampling, included grade V students from SDN Wangisagara 02 as the experimental class and SDN Toblong 02 as the control class, located in Majalaya District, Bandung Regency. The study's method was quasi-experimental, with a pre-and post-respond design using a non-equivalent control group design. The study's instrument was a learning outcome test instrument that passed the expert judgment validation process and instrument trials. The data analysis results show a significant difference in IPAS learning outcomes between the experimental and control classes. The mindful learning approach has a 38.56% effect on IPAS learning outcomes, while the conventional approach has a 30.47% effect. Keywords: Approach Learning; Mindful learning; IPAS Learning Outcomes